Use and abuse of law in the Athenian courts. - Chris Carey; Ifigeneia Giannadaki; Brenda Griffith-Williams (Editors) (Mnemosyne, Supplements, 2018)
This timely volume brings together leading scholars and rising researchers in the field to examine the role played by the law in thinking and practice in the legal system of classical Athens. The aim is not to find a single perspective or method for the study of Athenian law but to explore the subject from a variety of different angles. The focus of the collection on 'use and abuse' raises fundamental questions about the status of law in the Athenian constitution as well as the use of law(s) in the courts, the nature of law itself, and the elusiveness of a definition of 'abuse'. An introduction sketches the major developments in the field over the last century.